Variability Studies of Various Traits and Selection of Water Logging Tolerant Clones in Early Generation - Varija, G. Sai; Kumar, Balwant; Vennela, M. (International Journal of Bio-resource and Stress Management, 2024)
An experiment was carried out in January, 2021–December, 22 at Sugarcane Research Institute, Dr. RPCAU, Pusa, Samastipur, Bihar, India to screen the genotypes for tolerance to water-logging from July to September in the early clonal generation of sugarcane. The experimental design followed was augmented design, in which a total of 24 clones were planted together with 2 checks. The degree of genetic variability present in the base population and the heritability of the traits being improved will be key factors in any breeding programme success. For all of the observations, the analysis of variance indicated highly significant differences among the clones. The range of variation in mean value was comparatively wide for number of shoots at 120 DAP, plant height, number of millable canes and cane yield. The traits cane yield and sucrose content play a crucial role in selecting the appropriate clones. Thus, from the studies the clone CoX 20069 recorded the highest mean performance for cane yield. Whereas the genotype CoX 20068 showed the highest mean performance for HR Brix in November, December and January. Based on the brix value, cane yield and morphological performance eight clones namely CoX 20069, CoX 20068, CoX 20055, X 20030, X 20035, CoX 20054, CoX 20056, CoX 20246 can be selected for further utilization in breeding programme under water- logging condition. All the clones in the present study had non-flowering and non-lodging morphological behaviour.